Health economics of percutaneous hemodynamic support in the treatment of high-risk cardiac patients: a systematic appraisal of the literature. (June 2014) - Maini, Brijeshwar; Scotti, Dennis J; Gregory, David
Abstract : This article systematically appraises the findings and conclusions derived from six recent studies of the economic impact and relative value of using percutaneous ventricular assist devices to render short-term hemodynamic support to high-risk patients with particular attention to the settings of cardiogenic shock and percutaneous coronary interventions. Although the extant body of literature is still growing, these studies offer evidence and insight regarding the health economics of traditional and emerging technologies in this treatment domain, and generally find the latter to be cost-effective in the long term. As the incidence of heart disease rises and the attendant economic burden of healthcare climbs, technologies for mitigating cardiovascular illness will be the target for more robust empirical evidence to justify the comparative value of minimally invasive hemodynamic support interventions in the armamentarium of treatment options available to physicians.